Avaliação do potencial antigenotóxico da melatonina em células somáticas de Drosophila melanogaster irradiadas com raios gama - Lopes, Eloiza Peres Rodrigues (2000)
In view of the need to identify substances that can exert protective effects against agents that damage men’s health, this work evaluated the genotoxic and antígenotoxíc poíential of melatonin, using the Somatic Mutation and Recombination Test (SMART) in the somatic cells of Drosophila melanogaster. Standard (ST) and high bioactivation (HB) crosses were performed. The HB cross present a high levei of cytochrome P-450 enzymes. From both crosses marker-trans-heterozygous and balancer-heterozygous flies were obtaíned. Larvae of the third instar were submitted or not to pretreatment with different concentrations of melatonin (1.0; 2.5 and 5.0 mg / ml) and subsequently were irradiated or not with gamma rays (10 Gy). The test permitted the Identification of mutant hairs on the wings of the fruit fly, and also quantification of the mutation and recombination rate induced by the genotoxic agent. Our experimental results demonstrated that melatonin does not have genotoxic effects, and that it exerts protection against the effects caused by gamma rays in marker-trans-heterozygous descendents of ST cross. Analysis of the balancer-heterozygous flies revealed that the effects caused by gamma radiation were due mainly to recombination, and the radioprotection of melatonin was due only to the anti-recombinagenic effects. Differences were found between the results of standard and high bioactivation crosses, which suggests a possible interacfion between melatonin and cytochrome P-450 er>zymes. Considering these results it may be concluded that under appropriated 'aboratory conditions, melatonin may reduce gamma radiation damage.